Mejorando el intercambio de conocimientos a través de colaboraciones basadas en la confianza y liderazgo transformacional; Improving knowledge sharing through trust-based collaboration and idealized influence transformationa - Suhana Suhana; Suharnomo; Fuad Mas'ud; Anwar Mansyur (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– The aim of the current research is to examine the effect of trust-based collaboration and idealized transformational leadership to the knowledge sharing. It also examined the effect of contingent reward transactional leadership to trust-based collaboration and knowledge sharing. Data used in the current research are primary ones derived from questionnaires distributed to selected respondents. All lecturers of private universities in Central Java Indonesia having A qualification in institutional accreditation are the population. The sample is part of the population. Sampling technique used is non probability sampling, not all population has the same opportunity to be sample. The reason is that population is homogeneous in nature. The sample analysed is 162 respondents. The research finding indicates that idealized influence transformational leadership positively affects to trust-based collaboration. Trust-based collaboration has a positive effect on knowledge sharing. The research fails proving the effect of contingent reward transactional leadership to trust-based collaboration and knowledge sharing. Thus, the current research contributes to literature concerning the importance of trust-based collaboration in increasing knowledge sharing. The study is the first study examining the role of trust-based collaboration to the relationship between idealized influence transformational leadership and knowledge sharing. Trust-based collaboration is the novelty of the research, that is derivation of the two theories. The finding strengthens one of main flows in literature and gives more empirical evidence about the relationship between transformational leadership and knowledge sharing that the relationship between the two is indirect in nature.
Keywords: I22; J22; 330; Transformational leadership; trust; based collaboration; knowledge sharing